Preventing future pandemics using "one health" approach in Nepal - Dangal, Binod; Khadka, Man Bahadur; KC, Archana; Ghimire, Rajesh (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Emerging and re-emerging infectious diseases are in rise due to rapid climate change, environmental changes and population increase. COVID-19 has taught us about different understanding of health. One Health is a concept that recognizes the interconnections and health interdependencies among humans, other animals and the shared environments. The concept of One Health is in embryonic stage in Nepal. With the One Health approach, implementing systematic zoonotic surveillance, regulated rational use of antibiotics, prevention strategies through wide vaccination campaigns, global collaboration, rapid control of outbreaks with containment measures, development of zoonotic registry in the country, multisector coordination can prevent future pandemics.